1999
DOI: 10.1029/1999jd900802
|View full text |Cite
|
Sign up to set email alerts
|

Use of observed ice crystal sizes and shapes to calculate mean‐scattering properties and multispectral radiances: CEPEX April 4, 1993, case study

Abstract: Abstract.During the Central Equatorial Pacific Experiment, ice crystal sizes and shapes were measured in an outflow anvil. A habit (i.e., column, bullet rosette, Koch fractal polycrystal, sphere) was assigned to each particle using a self-organized neural network based on simulations of how the maximum particle dimension and area ratio varied for random orientations of these crystals. Average ice crystal size and shape distributions were calculated for 25 km long segments at six altitudes using measurements fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 28 publications
1
50
0
Order By: Relevance
“…Both simulations are compared with the same observational data from KWAJEX and TOGA-COARE, including some new cloud-related and thermodynamical statistics in the validation. Following Phillips et al (2007), the predicted properties of cirrus for TOGA-COARE are compared with observations from the Central Equatorial Pacific Experiment (CEPEX; McFarquhar et al, 1999), in view of the lack of flights above the freezing level during TOGA-COARE. Note that these maritime simulations (KWAJEX, TOGA-COARE) are not used for any biological sensitivity tests anywhere in the present paper.…”
Section: Appendix a Validation Of Simulations Of Maritime Convectionmentioning
confidence: 99%
“…Both simulations are compared with the same observational data from KWAJEX and TOGA-COARE, including some new cloud-related and thermodynamical statistics in the validation. Following Phillips et al (2007), the predicted properties of cirrus for TOGA-COARE are compared with observations from the Central Equatorial Pacific Experiment (CEPEX; McFarquhar et al, 1999), in view of the lack of flights above the freezing level during TOGA-COARE. Note that these maritime simulations (KWAJEX, TOGA-COARE) are not used for any biological sensitivity tests anywhere in the present paper.…”
Section: Appendix a Validation Of Simulations Of Maritime Convectionmentioning
confidence: 99%
“…The aspect ratio of the polycrystal remains invariant with respect to size. McFarquhar et al (1999) integrated the ice crystal shape distribution over the observed size distribution functions to obtain the bulk scattering properties to try to describe the reflectance properties of cirrus measured at four wavelengths between 0.664 µm and 2.142 µm obtained during the CEPEX (Central Equatorial Pacific Experiment) campaign. They found that the simulations of observed reflectances were highly sensitive to assumptions about which shapes to include in their shape distribution function, and a general description of cirrus reflectance would be difficult without prior knowledge of ice crystal shapes.…”
Section: Introductionmentioning
confidence: 99%
“…McFarquhar et al (1999) assumed an ensemble consisting of spheres, hexagonal ice columns, bulletrosettes and polycrystals. The polycrystal due to Macke et al (1996a) is a randomization of a second generation triadic Koch fractal and is supposed to represent the more irregular shapes that are observed in cirrus.…”
Section: Introductionmentioning
confidence: 99%
“…The larger cloud-ice mass increases the reflectivity of clouds and, hence, tends to increase the reflectivity of incident solar radiation on clouds in the control run than in the single-moment run. The in-cloud averaged generalized effective size of cloud ice is larger in the control run than in the single-moment run where the generalized size is prescribed as a function of air temperature following McFarquhar et al (1999) (Fig. 8d).…”
Section: Radiation (Arm-a Case)mentioning
confidence: 99%
“…Due to the absence of the particle-number prediction, the effective particle size diameter of a cloud droplet is assumed to be 20 μm, and that of cloud ice is given by empirical functions of height (McFarquhar et al 1999). The homogeneous freezing of all supercooled droplets and rain is performed at -36°C or below.…”
Section: Single-moment Microphysicsmentioning
confidence: 99%